Cyclodextrin-mediated formation of porous RNA nanospheres and their application in synergistic targeted therapeutics of hepatocellular carcinoma. (December 2020) - Chen, Xiaoxia; Chen, Tianshu; Zhang, Lili; Wang, Zhenyu; Zhou, Qingqing; Huang, Tingting; Ge, Chao; Xu, Huili; Zhu, Miaoxin; Zhao, Fangyu; Yao, Ming; Tian, Hua; et al.
Abstract: Spherical and porous nanoparticles are ideal nanostructures for drug delivery. But currently they are mainly composed of non-degradable inorganic materials, which hinder clinical applications. Here, biological porous nanospheres using RNA as the building blocks and cyclodextrin as the adhesive were synthesized. The RNA contained the aptamer of EpCAM for targeting delivery and siRNA for gene silencing of EpCAM, while cyclodextrin could load insoluble sorafenib, the core drug of targeted therapy for hepatocellular carcinoma (HCC), through its hydrophobic cavity. After being internalized into targeted HCC cells under the assistance of the aptamer, the porous nanospheres could be degraded by the cytoplasmic Dicer enzymes, releasing siRNA and sorafenib for synergistic therapy. The synergistic efficacy of the porous RNA nanospheres has been validated at in vitro function assay, subcutaneous tumor bearing mice, and orthotopic tumor bearing mice in vivo models. In view of the broad prospects of synergy of gene therapy with chemotherapy, and the fact that RNA and cyclodextrin of the porous nanospheres can be extended to load various types of siRNA and small molecule drugs, respectively, this form of biological porous nanospheres offers opportunities for targeted delivery of suitable drugs for treatment of specific tumors. Graphical abstract: Image 1 Highlights: Unique porous nanostructures were obtained using soft materials. RNA worked as building blocks and cyclodextrin as adhesives. Both siRNA (gene drugs) and sorafenib (chemo drugs) can be encapsulated. Synergistic treatment of hepatocellular carcinoma was achieved. The efficacy was validated using both subcutaneous and orthotopic tumor models.